Islam and Information - S. Abdullah Schleifer (International Institute of Islamic Thought, 1986)
I. INDEPENDENT NEWS AGENCIES Four major international news agencies-Associated Press, Reuters, United Press and Agence France Presse-gather and distribute much if not most of the international news (be it “hard,” breaking news or “soft” news features) published and broadcast in the world? They transmit in English and French as well as a number of commercially significant and logistically easy regional languages. (A.P. transmits a daily service in English, French, Spanish, German, Dutch, Swedish and offers an Arabic features service by mail. Reuters and AFP offer a daily news file in Arabic.) Most of this news is now transmitted point-to-point either by landline, microwave link, satellite or some combination of these methods which have largely replaced radio wireless transmission over the past ten years. The new technology is much more effective; much less subject to failure and climatic interference but much more expensive. Point-to-point telex is also sometimes used as a fall back position where radio wireless transmission is still in use. The Associated Press, as an example, has 8,500 subscribers in 150 countries outside of the United States for its World Service. But the extent that Big Four news dominates international news is much greater than the number of subscribers would indicate, since many national news agencies subscribe to one or more of the Big Four services and then edit and re-transmit the material as part of their own news service to hundreds or even thousands of local news outlets; e. g. Tass-which subscribes to the Associated Press service-has approximately 6,000 subscribers in the Soviet Union. As the number of full-time foreign correspondents for newspapers continues to decline due to increasing costs and as mass media has proliferated throughout the Third World over the past few decades, the Big Four and other news agencies have expanded in size ...